Nativity in the healthy migrant effect: Evidence from Australia - Guogui Huang; Fei Guo; Zhiming Cheng; Lihua Liu; Klaus F. Zimmermann; Lucy Taksa; Massimiliano Tani; Marika Franklin (Elsevier, 2023)
Migrant health constitutes an important public health issue; however, variations in the 'healthy migrant effect' among migrants of different nativity are not adequately understood. To fill this gap, this study examines the life expectancy (LE) and healthy life expectancy (HLE) of the Australian-born population and eight major migrant groups in Australia for 2006, 2011 and 2016. The results show that compared with the Australian-born population, the foreign-born population overall had a higher LE and HLE but a lower HLE/LE ratio. Considerable variations in migrant health status according to nativity were also observed. Specifically, migrants from South Africa, Britain and Germany exhibited a similar or higher LE, HLE and HLE/LE ratio, while those from China, India, Italy and Greece had a higher LE but a significantly lower HLE/LE ratio compared with the Australian-born population. Lebanese migrants were the only group who experienced an unchanging LE and a declining HLE from 2006 to 2016. These notable differences in migrants' health outcomes with respect to nativity may be explained by the sociocultural differences between the origin and host countries and the different extents of migration selectivity of different migrant groups. Targeted countermeasures such as improving the quality of life of migrants from culturally diverse backgrounds or with negative migration experiences are suggested.